Pelaksanaan Gerakan Literasi di Sekolah Dasar Kampar dan Pekanbaru - Natasya Meisandi Putri; Ridia Syafitri; Riva Gusnaida; Febrina Dafit (Universitas Nusantara PGRI Kediri, 2023)
Literacy is the key to unlocking students' knowledge and insight. Good literacy skills in students will enable students to develop themselves optimally so that something good is achieved too. To achieve good literacy skills, literacy learning is the main thing that must be carried out well, especially at the elementary level. The purpose of this research is to describe literacy learning in elementary schools. This research was conducted to find out how literacy programs were implemented in several elementary schools in Kampar and Pekanbaru City. The elementary schools that were used as research objects were SDN 21 Pekanbaru, MIN 3 Pekanbaru, and SDN 017 Pandau Jaya which covered several literacy levels such as literacy, scientific literacy, numeracy, financial literacy, digital literacy, and cultural-citizenship literacy. This article is written using a method based on observation results by conducting interviews and direct observation of literacy activities carried out in elementary schools. The results of this study are useful for adding insight into the successful implementation of the literacy program, the challenges faced and suggestions for good implementation.